Kebijakan Moneter Tanpa Bunga - Irwan Maulana; Ruslan Husein Marasabessy (Jurnal Asy-Syukriyyah, 2018)
The central bank as the monetary authority uses several monetary instruments including the application of interest rates to create monetary stability. Interest has determined every economic activity, such as consumption, savings, investment, employment opportunities, export-import, and others. This study aims to describe the assumptions of how to conduct monetary policy without interest, using qualitative methods through library research. As for the background of this research, there are some fatwa in Muslim countries regarding the prohibition of interest while interest as monetary instruments. This research will contribute to the body of existing literature of Islamic economic development.